2018
DOI: 10.3390/beverages4010002
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Carrier Quantity and Drying Method on the Physical Properties of Apple Juice Powders

Abstract: Abstract:The study aimed at the evaluation of the physical properties of apple juice powders mixed with different concentration of maltodextrin obtained by freeze-, vacuum and spray drying methods. Due to the chemical composition of apple juice there was a possibility to obtain apple juice powders by freeze-, spray and vacuum drying, excluding vacuum drying at 40 • C when 15% and 20% of maltodextrin were added. The moisture content of powders was more dependent on the drying method than on the quantity of malt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
29
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 31 publications
8
29
0
2
Order By: Relevance
“…In general, the spray-drying process resulted in a lower moisture content (approximately 87%) in comparison to powders gained after the freeze-drying process, regardless of the type of carrier and the concentration used for the preparation of feed solutions. A similar observation was made in case of apple powders [31]. Likewise, in the studies on the watermelon, Gac, and ginger juice [14,[32][33][34], it was observed that a higher content of carrier in the feed solution resulted in a lower moisture content of the powders obtained, pointing to a strong influence of the carrier concertation on the powders' final properties.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…In general, the spray-drying process resulted in a lower moisture content (approximately 87%) in comparison to powders gained after the freeze-drying process, regardless of the type of carrier and the concentration used for the preparation of feed solutions. A similar observation was made in case of apple powders [31]. Likewise, in the studies on the watermelon, Gac, and ginger juice [14,[32][33][34], it was observed that a higher content of carrier in the feed solution resulted in a lower moisture content of the powders obtained, pointing to a strong influence of the carrier concertation on the powders' final properties.…”
Section: Discussionsupporting
confidence: 73%
“…In the powders obtained after freeze-drying, lower water activity and lighter color were noticed, whereas, after spray-drying, higher water activity and a darker color of powders were indicated. In the studies performed by Michalska and Lech [31], powders of the apple juice containing maltodextrin were lighter after the freeze-drying process when compared to spray-drying. When the coordinate a* was concerned, the increase in the concentration of the carrier caused a decrease in the a* values.…”
Section: Concentration Of Carriermentioning
confidence: 99%
See 2 more Smart Citations
“…The bulk density for present study (Table ) varied from 0.37 to 0.63 g cm −3 which falls within the limit for food powders, however, crossed the lower limit of skim milk powders due to the higher fat content (12.38%) in the rapeseed bee pollen (when added at a rate of 15% rather than 5%). Moreover, the vacuum drying causes the bigger size of particles (crystallized structure) thus resulting in the higher bulk density of powders than the freeze and spray drying (Michalska & Lech, ). The linear effects of pollen ( x 1 ) and temperature ( x 2 ) were strongly significant ( p < .0001) for bulk density showing the increase in bulk density on reducing the pollen and temperature (Figure ).…”
Section: Resultsmentioning
confidence: 99%